Behaviour based safety implementation and comparison in a chemical manufacturing industry - Siti Nurlaily Muhamad Yussof, 1988-; Mat Rebi Abdul Rani; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2014